The Evaluation of Implementation of Inclusive Education in West Sumatera - Nurhastuti Nurhastuti; Irdamurni Irdamurni; Damri Damri; Jehan Nabela Oktaviani (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
The implementation of inclusive education in West Sumatera has been on 6 (six) years. In this period it has shown a fairly long journey. Therefore, the implementation of inclusive education in West Sumatera is comprehensively evaluated for the realization of the inclusive education goals. The evaluation process itself will be useful to see the inclusive values that have occurred in primary schools that serve students with special needs in West Sumatra. The result of this research is the context component which covers the policy aspect of the program implementation, the program objectives and the context of its relation with the social culture of the society has not been fully implemented properly. The input components covering aspects of learners (students), educators (teachers), curriculum, infrastructure facilities, and financing the implementation of programs in inclusive schools have not been fully implemented properly. Process components that include aspects of learning planning activities, implementation of learning, and evaluation of learning and difficulties faced by teachers in teaching children with special needs in inclusive schools have not been fully implemented properly. Product components that include aspects of academic development of children with special needs and aspects of social skills development of students in inclusive schools can be said to have been implemented properly.